Tweets – Hashtag Strategy For Currency Ban (Trinity Journal of Management, IT & Media (TJMITM), 2017)
T – H      Indian Government made a high-chance, high-stakes financial  mediation on the world's biggest Democratic state, with a goal to  diminish corruption from the country. Overnight, 86% of cash  trade flow was voided. Nation's right around 90% cash money  dependent were disturbed due to the ban of certain currency  th notes which resulted in Demonetization after 25 years of  economic reforms that changes many paradigms in the Indian  nation not only in terms of economically but also affected many  other domain areas like lifestyle, health, infrastructure and the  fourth pillar of the society i.e. media and entertainment sector too.  The Blame game as well as the games to build the positive aura  to fill the scars of demonetization started via use of the effective  tool called New media specially using the hash tags i.e. Twitter.  As we know social media is a game changer in the political  campaigns, it also helped the country during the demonetization  period. The communication skills on twitter have come into sharp  focus in the past three to four months during the self created crisis  of the government, when they rendered Rs. 500 and Rs. 1000  notes. Despite of several criticisms from the public and the other  political parties of the hardship caused by the demonetization  process around 90% of the population supported this move. The study is all about how the new media especially the twitter  helps created the positive aura to the masses and specially the  citizen of republic of India or not during the demonetization  period when there was hustle bustle everywhere. The study will  also deals with different analyses of the tweets done at the time of  demonetization phase
Keywords: Tweets; Hashtag; Demonetization; New Media